Jasadiyah Education in Modern Pesantren with Multicultural and Democratic Style - Iqbal, Muhammad; Chaghtai, Kaleem; Nath, Arjun; Garcia, Camila; Al-Mutawakkil, Thufail; Afiyah, Ishmah; Husna Srifyan, Jihan (Solo Universal Journal of Islamic Education and Multiculturalism, 2023)
Jasadiyah education emphasizes developing the physical, mental, and spiritual aspects of individuals. In the context of multicultural and democratic education, jasadiyah education aims to form individuals who have a deep understanding of cultural diversity and democratic values. The methods used in jasadiyah education in this context include a holistic approach that blends physical, intellectual, and spiritual learning. This is done through the introduction of concepts such as tolerance, empathy, and mutual respect for diversity. This approach also includes students' active participation in the learning process, allowing them to learn from different experiences and perspectives. The result of jasadiyah education in the view of multicultural and democratic education is the formation of individuals who have a deep understanding of democratic values, understand and appreciate cultural diversity, and can contribute positively to a multicultural society. They will also be agents of change capable of promoting peace, tolerance, and cross-cultural understanding. Other main results are jasadiyah education in Islam includes: Following health rules of eating and drinking, Fortifying themselves from infectious diseases, Treating diseases, Applying the principle of not endangering themselves and others, Getting children to love sports and riding mounts, Familiarizing children with zuhud and not dissolving in pleasure, Instilling Character Earnest and officers.